Endodontically treated primary second molar giving rise to formation of dentigerous cyst - Chakraborty, Somnath; Rastogi, Pradeep (Asian Journal of Medical Sciences, 2017)
The primary teeth with infected root canals, especially in those cases in which infection has spread to the periradicular tissues are common problem associated with primary dentition. Thus in the feld of pediatric dentistry, pulpectomy is considered to be the safe, commonest and successful treatment procedure for primary dentition with periapical inﬂammation. Sometimes even after pulpectomy, there remains some residual periapical infection which can lead to some complications like dentigerous cyst.Dentigerous cyst is an epithelial-lined developmental cavity that encloses the crown of an unerupted tooth at the cementoenamel junction. The present case report describes a case of a 9 year old boy whose primary second molar was pulpectomizedand later on lead to the development of a dentigerous cyst. Asian Journal of Medical Sciences Vol.8(2) 2017 90-93